2021
DOI: 10.1093/ofid/ofab125
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Time-Out for Vancomycin by Infectious Disease Physicians Versus Clinical Pharmacists: A Before-After Crossover Trial

Abstract: Background The present study assessed the impact of time-out on vancomycin use and compared the strategy’s efficacy when led by pharmacists versus infectious disease (ID) physicians at a tertiary care center. Methods Time-out consisting of a telephone call to inpatient providers and documentation of vancomycin use > 72 hours was performed by ID physicians and clinical pharmacists in the Departments of Medicine and Surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…To evaluate the effect of the ASP in this study, we measured processes such as changes in antibiotic use and outcomes associated with these changes. Although the DOT as a process measure has been reported to decrease in prior studies, the effectiveness of ATOs in reducing mortality has not been determined (11–15). In this study, the difference in the hospital discharge rate was almost negligible (phase 1, 92.0%; phase 2, 93.7%) and not significant with the chi-square model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effect of the ASP in this study, we measured processes such as changes in antibiotic use and outcomes associated with these changes. Although the DOT as a process measure has been reported to decrease in prior studies, the effectiveness of ATOs in reducing mortality has not been determined (11–15). In this study, the difference in the hospital discharge rate was almost negligible (phase 1, 92.0%; phase 2, 93.7%) and not significant with the chi-square model.…”
Section: Discussionmentioning
confidence: 99%
“…A prescriber-driven ATO at 48 to 72 hours of treatment with paper or electronic medical record ATO tools has been reported to decrease inappropriate antibiotic therapy and days of therapy (DOT) with antibiotics (11)(12)(13). Similarly, pharmacistdriven ATO was reported to be associated with more frequent assessments and changes in antibiotic use (14) and was also more effective in reducing the use of vancomycin in comparison with interventions by ID specialists (15).…”
mentioning
confidence: 99%
“…24 A timeout intervention for vancomycin showed a decrease in weekly vancomycin days of therapy (DOT) per 1,000 patient day (coefficient, −0.49; P = .007) as well as a decrease antimicrobial usage in the pharmacist-led arm (coefficient, −0.77; P = .007) compared to an ID physician arm. 25 Finally, a study in Japan reported that clinical pharmacist involvement in an ASP team reduced the volume of antimicrobial prescriptions in a skilled nursing facility (incidence rate ratio [IRR], 0.885; P < .001) (Figure 1). 26 Several clinical-pharmacist-led ASP studies have been conducted in Thailand.…”
Section: Evidence On the Efficacy Of Pharmacist-driven Asps In Asiamentioning
confidence: 99%
“…They suggest that prospective review and feedback and pre-prescription restrictions are 2 of the most effective actions and as such will be reviewed first. 23 Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] summarized the actions employed and outcomes.…”
Section: Intervention By Typementioning
confidence: 99%
“…Summary of Studies Utilizing 1 Primary ASP Action and Impact on Anti-MRSA Therapy [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. …”
mentioning
confidence: 99%